Molecular characterization of guava (Psidium guajava L.) germplasm by RAPD analysis - Ahmed, B; Mannan, MA; Hossain, SA (International Journal of Natural Sciences, 2011)
Psidium guajava L. is a perennial fruit tree in subtropical and tropical areas. In Bangladesh, P. guajava has been used as edible fruits and people use it to treat acute diarrhea, cough and intestinal spasmodic diseases. In the present study, morphological and molecular characterizations were used to display different levels of variability. Molecular marker random amplified polymorphic DNA (RAPD) was used for the molecular identification of 33 P. guajava germplasm from three selected south-western location of Bangladesh. Among them, eleven commercially cultivated germplasm and the rest twenty two were collected from local farmers. The 10-mer and 12-mer oligonucleotide primers were used in RAPD to amplify. Four primers, A02, A03, S07 and S08, were able to direct the amplification and yield a total of 252 band patterns of which 33.19% were polymorphic. The highest percent of polymorphic loci (37.5%) was observed from primer A03 and the lowest (28.57%) was from primer S08. Results were analyzed by molecular algorithm UPGMA and Neighbor-Joining. Thirty-three genotypes on the dendrogram were identified and divided into two major groups and subgroups on the basis of morphological characteristics and also on the uncultivated and commercial cultivars. The range of genetic distance was observed 0.5253 (Jelly and Thai) to 0.6631 (V30 and V 22). Based on the cluster analysis, the P. guajava samples have morphological difference were grouped independently. The results suggested that RAPD is useful for the discrimination of uncultivated, cultivars P. guajava for high economy. Key words: Guava; Germplasm; RAPD; Marker; Dendrogram. DOI: http://dx.doi.org/10.3329/ijns.v1i3.8823 International Journal of Natural Sciences (2011), 1(3):62-67